Development of risk assessment tool for the land cargo transportation / Afzan Ahmad Zaini, Intan Rahani Endut and Abdul Azim Ahmad Zaini - Zaini, Afzan Ahmad; Endut, Intan Rahani; Zaini, Abdul Azim Ahmad (2013)
The purpose of this report is to present details of a study which has been undertaken with an aim of establishing a risk assessments tool for the logistics industry particularly the land cargo transportation in Malaysia. For the purpose of achieving this aim, three core objectives have been outlined which include investigating the type of risks faced by the land cargo transportation and logistics supply chain in general, evaluating the likelihood and impact of the risks and drawing systematic mitigation measures for the critical risks. The first objective was achieved using the risk identification process which was done by listing down all possible risks inherent in the industry. From the risk identification, 59 probable risks which could give adverse consequences to the industry were identified. Subsequently all 59 risks were categorized under 5 general risk groups designated as Environmental risk, Financial risk, Political risk, Social risk, and Technical risk. The second objective was materialised by adopting the principle of the risk assessment matrix in which not only the degree of the impact and likelihood were determined but also the severity of the risks themselves based on the quantitative analysis of the empirical data obtained from the questionnaire survey. The results revealed four risks namely "Rising fuel cost", "Economic recession", "Workers demand salary increment" and "Increase in maintenance cost" were critical to the industry. In addition, from the risk matrix, the reduction of risk as the response plan was mostly agreed by respondents to be the best response plan for all four critical risks. The third objective gave the elaboration to the risk response plan which was argued to be simplistic. Here, the mitigation measures were drawn from the fundamental aspects, causes, effects of the critical risks and subsequently the mitigation measures to be taken to alleviate the adverse consequences of the critical risks were proposed. Lastly a tool was established that composed of three assessment parts denoted as the risk identification, the risk assessment matrix and the risk mitigation measures.